Resistance of Leishmania (Viannia) Panamensis to Meglumine Antimoniate or Miltefosine Modulates Neutrophil Effector Functions - Regli, Ivo B.; Fernández, Olga Lucía; Martínez-Salazar, Berenice; Gómez, Maria Adelaida; Saravia, Nancy Gore; Tacchini-Cottier, Fabienne (Frontiers in Immunology, 2018)
Leishmania (Viannia) panamensis (L. (V.) p.) is the main causative agent of cutaneous leishmaniasis in Colombia and is usually treated with either meglumine antimoniate (MA) or miltefosine (MIL). In recent years, there has been increasing evidence of the emergence of drug-resistance against these compounds. Neutrophils are known to play an important role in immunity against Leishmania. These cells are rapidly recruited upon infection and are also present in chronic lesions. However, their involvement in the outcome of infection with drug-resistant Leishmania has not been examined. In this study, human and murine neutrophils were infected in vitro with MA or MIL drug-resistant L. (V.) p. lines derived from a parental L. (V.) p. drug-susceptible strain. Neutrophil effector functions were assessed analyzing the production of reactive oxygen species (ROS), the formation of neutrophil extracellular trap (NET) and the expression of cell surface activation markers. Parasite killing by neutrophils was assessed using L. (V.) p. transfected with a luciferase reporter. We show here that MA and MIL-resistant L. (V.) p. lines elicited significantly increased NET formation and MA-resistant L. (V.) p. elicited significantly increased ROS production in both murine and human neutrophils, compared to infections with the parental MIL and MA susceptible strain. Furthermore, neutrophils exposed to drug-resistant lines showed increased activation, as revealed by decreased expression of CD62L and increased expression of CD66b in human neutrophils. In contrast, L. (V.) p. lines resistant to either MA or MIL presented higher survival within neutrophils than the drug-susceptible strain. These results provide evidence that parasite drug-susceptibility influences neutrophil activation and function as well as parasite survival within neutrophils. Further studies on the impact of drug susceptibility on neutrophil effector function should contribute to better understanding of the factors involved in susceptibility to anti-Leishmania drugs.